The effects of augmented feedback on pacing and performance of elite combat athletes - Halperin, I. (Edith Cowan University, 2017)
Augmented feedback has been shown to improve performance and influence pacing in various physical activities. However, few studies have investigated its effects on performance and pacing in striking combat sports. Additionally, despite the plethora of studies examining the influence of feedback in untrained individuals, there is a lack of research examining the effects of such feedback in trained participants. Considering the important role of feedback in training and competition, the purpose of this thesis is to examine the effects of three different but inter-dependent methods of augmented feedback on performance of combat, and resistance trained athletes.